Manajemen Idarah dan Imarah Masjid Raya Al Hijri 2 Bogor - Firmansyah, Indra Muhammad (Komunika: Journal of Communication Science and Islamic Dakwah, 2019)
The function of the mosque is not only as a place of worship rituals. The mosque must have the function of community empowerment, economic improvement, the organization of Baitul Mal, zakat, infaq, and alms services. Therefore, mosque managers must realize that mosques have a huge role, at least for the mosque's congregation. The purpose of this study was to determine the management of the Al Hijri 2 Bogor Grand Mosque. This research is qualitative. They were collecting data through interviews, observation and documentation. The study results found that the management of the Masjid Raya Al Hijri 2 Idarah and its Imarah has been running smoothly. However, because the mosque is expanding, the function of the mosque in social and economic terms has not been going well. Abstrak Fungsi masjid bukan hanya sebagai tempat ritual ibadah. Masjid harus memiliki fungsi pemberdayaan masyarakat, peningkatan ekonomi, penyelenggaraan Baitul mal, pelayanan zakat, infak, dan sedekah. Oleh karena itu, pengelola masjid harus menyadari bahwa masjid memiliki peran yang sangat besar, sekurang kurangnya bagi jamaah masjid itu sendiri. Tujuan penelitian ini untuk mengetahui Manajemen Masjid Raya Al Hijri 2 Bogor. Penelitian ini merupakan penelitian kualitatif. Pengumpulan data melalaui wawancara, observasi dan dokumentasi. Hasil penelitian menemukan bahwa Manajemen Masjid Raya Al Hijri 2 Idarah dan Imarahnya sudah berjalan dengan lancar akan tetapi disebabkan masjid dalam proses perluasan maka fungsi masjid dalam bentuk sosial dan ekonomi belum berjalan dengan baik.